ANALYSIS OF THE GENETIC DIVERSITY IN MAIZE LANDRACE CULTIVARS FROM NORTHERN RIO GRANDE DO SUL, BRAZIL - ARGENTA, JÉSSICA; ACUNHA, JEFFERSON GONÇALVES; MACHADO, BIANCA OLIVEIRA; RIZZARDO, ARIEL; BISPO, NORYAM BERVIAN (REVISTA BRASILEIRA DE MILHO E SORGO, 2021)
Maize landraces are important genetic resources for maize breeding. Many of these landrace varieties have not yet been properly studied to be distinguished from the others. In this study, multivariate statistical methods were used, beyond the analysis of variance, for estimating genetic dissimilarity among 27 maize landrace accessions. Principal Component Analysis and clustering analysis were performed using 16 evaluated quantitative traits. The Analysis of Variance results reported the existence of significant differences among the tested accessions for 14 evaluated traits. The first principal component and the second one almost explained 49% of found experimental phenotypic variance. Four different clusters were formed by the used clustering analysis. The clusters differed in 11 traits by the Analysis of Variance. This result and the graphical integration of this dendrogram with the Principal Component Analysis allowed to conclude that the phenotypic variation found may be due to the genotypic distinctions existing among the four groups of accesses determined in this study.